SISTEM INFORMASI PERSEDIAAN BERBASIS DESKTOP PADA BENGKEL ENGGAL PINTU - Ningsih, Neng Sari Ratna Widya; Paryati, Retno (Journal of Economics, Accounting, Tax, and Management (JECATAMA), 2024)
This study aims to determine the procedure, design, and to implement an inventory information system at the Enggal Pintu Garage. The method used in designing and implementing the system at the Enggal Pintu Garage is a descriptive method with a qualitative analytical approach, with the PIECES analysis method and the system development method using Software Development Life Cycle (SDLC) model with the waterfall mode and system testing using Black Box testing and User Acceptance Test (UAT). The software used in implementing the system is Microsoft Visual 2022 with a MySQL database. The results of testing and implementation show that the system functions well. Among them the system can display, add, delete, change, and close transactions entered so that the resulting output is in accordance with the input that has been processed. The output generated by the system includes goods reports, incoming goods reports, outgoing goods reports, return goods reports, demand reports, and stock inventory reports, which can be adjusted according to user needs.  Keywords: Information System, Inventory, Microsoft Visual Studio 2022, PIECES, Waterfall